Hypothermia therapy for newborns with hypoxic ischemic encephalopathy - Rita C. Silveira; Renato S. Procianoy (Brazilian Society of Pediatrics, 2015)
Objective: Therapeutic hypothermia reduces cerebral injury and improves the neurological outcome secondary to hypoxic ischemic encephalopathy in newborns. It has been indicated for asphyxiated full‐term or near‐term newborn infants with clinical signs of hypoxic‐ischemic encephalopathy (HIE). Sources: A search was performed for articles on therapeutic hypothermia in newborns with perinatal asphyxia in PubMed; the authors chose those considered most significant. Summary of the findings: There are two therapeutic hypothermia methods: selective head cooling and total body cooling. The target body temperature is 34.5 °C for selective head cooling and 33.5 °C for total body cooling. Temperatures lower than 32 °C are less neuroprotective, and temperatures below 30 °C are very dangerous, with severe complications. Therapeutic hypothermia must start within the first 6 hours after birth, as studies have shown that this represents the therapeutic window for the hypoxic‐ischemic event. Therapy must be maintained for 72 hours, with very strict control of the newborn's body temperature. It has been shown that therapeutic hypothermia is effective in reducing neurologic impairment, especially in full‐term or near‐term newborns with moderate HIE. Conclusion: Therapeutic hypothermia is a neuroprotective technique indicated for newborn infants with perinatal asphyxia and HIE.